The Philosophy of education - Mead, George Herbert; Biesta, Gert.; Tröhler, Daniel (Boulder, London : Pradigm Publisher, 2008)
Collaborating with the genius of C.S. Lewis, and particularly his brilliant work The Abolition of Man, the authors offer a multi-facetted, interdisciplinary investigation of perennial questions that impact human development and freedom.
Includes bibliographical reference and index.
Keywords: Education .